2021
DOI: 10.1021/acssynbio.1c00335
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Wired Life: Synthetic Biology for Electroactive Bacteria

Abstract: Electroactive bacteria produce or consume electrical current by moving electrons to and from extracellular acceptors and donors. This specialized process, known as extracellular electron transfer, relies on pathways composed of redox active proteins and biomolecules and has enabled technologies ranging from harvesting energy on the sea floor, to chemical sensing, to carbon capture. Harnessing and controlling extracellular electron transfer pathways using bioengineering and synthetic biology promises to heighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 195 publications
0
47
0
Order By: Relevance
“…Various studies on electrochemical evaluation of different microorganisms from various environments and their 16 s rRNA gene sequence analysis indicate that more phylogenetic and physiologically diverse microorganisms may be successfully used as in the MFC assembly (Naradasu et al 2019). A number of pure cultures have already been identified that can conduct EET with suitable electrodes from a variety of habitats (Zuo et al 2008;Bird et al 2021). One such source is the cow's intestine, which has a reductive and an anaerobic setting, where fermentation is the predominant mode of microbial metabolism in which nicotinamide adenine dinucleotide (NADH) induces the reduction and oxidation of organic substrates (De Menezes et al 2011;Fritts et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on electrochemical evaluation of different microorganisms from various environments and their 16 s rRNA gene sequence analysis indicate that more phylogenetic and physiologically diverse microorganisms may be successfully used as in the MFC assembly (Naradasu et al 2019). A number of pure cultures have already been identified that can conduct EET with suitable electrodes from a variety of habitats (Zuo et al 2008;Bird et al 2021). One such source is the cow's intestine, which has a reductive and an anaerobic setting, where fermentation is the predominant mode of microbial metabolism in which nicotinamide adenine dinucleotide (NADH) induces the reduction and oxidation of organic substrates (De Menezes et al 2011;Fritts et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In bacteria, antibiotic resistance genes are commonly selected for this purpose [ 143 ]; however, the use of auxotrophic markers has also been described [ 144 ]. Outside of established systems, recent studies have continued to develop new types of reporters, including genes producing electrical signal [ 145 ], gas production [ 146 ], and targeted genome editing [ 147 , 148 ].…”
Section: Methods For Improving Bacterial Biosensor Propertiesmentioning
confidence: 99%
“…When using less common reporter genes, however, more complex or specialized equipment can be required. For example, reporters producing electroactive signal can require a bioelectronic sensing system [ 145 ]. In previous work using reporters that function through gas production, a gas chromatograph-mass spectrometer (GC-MS) was required [ 146 ].…”
Section: Methods For Improving Bacterial Biosensor Propertiesmentioning
confidence: 99%
“…[ 16–19 ] Many studies have explored ways to improve the MFC performance through nanotechnologies, genetic engineering of bacteria, and material innovations. [ 13,20,21 ] However, their integration into the large‐scale footprint cost‐effectively and robustly is questionable. Although stacking of modular small MFC units has been proposed as an alternative solution for large‐scale development, the performance has not noticeably improved because of intrinsic voltage reversal and mass transport limitations within the serially connected units.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Many studies have explored ways to improve the MFC performance through nanotechnologies, genetic engineering of bacteria, and material innovations. [13,20,21] However, their integration into the large-scale footprint cost-effectively and robustly is questionable. Although stacking of modular Considerable research efforts into the promises of electrogenic bacteria and the commercial opportunities they present are attempting to identify potential feasible applications.…”
mentioning
confidence: 99%